Mechanisms of Azole Resistance in Petite Mutants of Candida glabrata - Brun, Sophie (American Society for Microbiology, 2004)
We previously showed that resistant colonies of Candida glabrata inside the azole inhibition zones had respiratory deficiency due to mutations in mitochondrial DNA. Here, we analyzed the mechanisms of azole resistance in petite mutants of C. glabrata obtained by exposure to fluconazole or induced by ethidium bromide. The respiratory deficiency of these mutants was confirmed by oxygraphy and flow cytometric analysis with rhodamine 123, and its mitochondrial origin was demonstrated by transmission electron microscopy and restriction endonuclease analysis of the mitochondrial DNA. Flow cytometry with rhodamine 6G suggested an increased drug efflux in mutant cells, which was further supported by Northern blot analysis of the expression of the C. glabrata CDR1 (CgCDR1) and CgCDR2 genes, encoding efflux pumps. Conversely, the expression of CgERG11, which encodes the azole target, was not affected by petite mutations, and no differences were seen in the sequence of this gene between parent isolates and mutants. Moreover, sterol analysis showed similar overall amount of sterols in parent and mutant cells, but quantitative modifications were observed in the mutants, with almost undetectable biosynthesis intermediates. Further analysis performed after separation of free sterols from steryl esters revealed a defect in sterol esterification in mutant cells, with free ergosterol representing 92% of the overall sterol content. Thus, resistance or decreased susceptibility to azoles in petite mutants of C. glabrata is associated with increased expression of CgCDR1 and, to a lesser extent, of CgCDR2. In addition, the marked increase in free ergosterol content would explain their increased susceptibility to polyenes.